Navigating Religious Hegemony and Human Rights Based on KUHP: Al-Zaytun's Controversial Case - Dewantri, Puja Alviana; Pattiserlihun, Selvone Christin; Hakim, Putri Rahmah Nur (Institut Agama Islam Negeri Fattahul Muluk Papua, 2023)
The Al-Zaytun issue has ignited a heated debate in Indonesia about religious pluralism, religious freedom, and human rights. This quandary, reminiscent of the Indonesian Ahmadiyya Muslim Congregation's situation classified as